Basel III’s Corporate Governance Impact: How Increased Banking Regulations Pose Challenges to Corporate Compliance While Simultaneously Furthering Stakeholder Objectives - Howard , Cory (Journal of Law and Governance, 2014)
Basel III was primarily intended to provide additional regulations to prevent the collapse of financial institutions during times of liquidity crises. However, two primary reforms, namely the new capital adequacy framework and disclosure requirements, will not only prevent banks from failure during periods of financial distress, but also help promote corporate governance objectives. In the traditional model of corporate governance, shareholders will benefit from the stability of firms in which they have invested, as well as having access to accurate and complete financial statements. Additionally, non-shareholder stakeholders will benefit from increased systemic stability and avoiding the resulting problems that the 2007 financial collapse created, such as decreased access to consumer credit, stagnant wages, and skyrocketing unemployment. This article will attempt to outline the specific corporate governance benefits that Basel III will bring, focusing on how disclosure requirements and capital adequacy will help shareholders and stakeholders alike.